Assessing the impact of the COVID-19 pandemic on neglected tropical diseases in India: a perspective - Zaidi, Ilham; Vardha, Jagadeeswari; Khayum, Abdul; Anjum, Sahifa; Chaudhary, Shikhar; Bakshi, Aditi; Gill, Jasmeen Kaur (Frontiers in Public Health, 2024)
The COVID-19 pandemic has significantly challenged healthcare systems worldwide, particularly in India, a country already burdened with a high prevalence of Neglected Tropical Diseases (NTDs). This perspective examines the pandemic's direct and indirect impacts on the prevalence, diagnosis, and management of NTDs in India.Using a narrative review approach, we analyzed literature published between January 2020 and September 2023 from databases such as PubMed, Scopus, and Google Scholar, along with grey literature. The focus was on studies reporting the pandemic's influence on NTDs, especially among vulnerable populations in both rural and urban settings.The review incorporated 49 studies, revealing a twofold impact of COVID-19 on India's healthcare. Directly, the surge in COVID-19 cases strained healthcare resources, disrupted services, and overwhelmed healthcare personnel. Indirectly, the pandemic exacerbated the burden of NTDs by delaying diagnoses, limiting access to treatment, and redirecting resources toward pandemic response efforts.These findings highlight the urgent need for resilient healthcare strategies that address both the immediate and long-term impacts of the pandemic on NTDs. By understanding and mitigating these effects, policymakers and public health experts can better protect vulnerable populations from the compounded challenges posed by these neglected diseases.